2002
DOI: 10.1029/2001je001588
|View full text |Cite
|
Sign up to set email alerts
|

Multiyear Mars Orbiter Camera (MOC) observations of repeated Martian weather phenomena during the northern summer season

Abstract: [1] The Mars Global Surveyor Mars Orbiter Camera (MGS MOC) has observed several atmospheric events repeat within a few degrees of L s from one year to the next over 3 Mars years during a portion of the northern summer, southern winter seasons (L s = 124°-140°). The repeatability suggests a previously unobserved lack of significant variation in the present Martian northern summer seasonal climate. Nonetheless, interannual variations in the seasonal south polar cap and in the residual north polar cap were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
75
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 46 publications
11
75
0
Order By: Relevance
“…3 (left). The discrete ordinate multiple scattering code developed for general use by Stamnes et al (1988) has been adapted to Mars atmospheric application for both aerosol (Clancy and Lee, 1991;Wolff et al, 1999;Clancy et al, 2003) and ozone (James et al, 1994;Clancy et al, 1995Clancy et al, , 1999 retrievals, and is employed here. In the current model configuration, developed by Wolff et al (2002), we specify spatial variation in the Rayleigh scattering column associated with topography (dotted line in Fig.…”
Section: Ozonementioning
confidence: 99%
“…3 (left). The discrete ordinate multiple scattering code developed for general use by Stamnes et al (1988) has been adapted to Mars atmospheric application for both aerosol (Clancy and Lee, 1991;Wolff et al, 1999;Clancy et al, 2003) and ozone (James et al, 1994;Clancy et al, 1995Clancy et al, , 1999 retrievals, and is employed here. In the current model configuration, developed by Wolff et al (2002), we specify spatial variation in the Rayleigh scattering column associated with topography (dotted line in Fig.…”
Section: Ozonementioning
confidence: 99%
“…The albedo measurements used here were taken within Martian year MY24, which was characterised by minimal localised dust storm events [97], and a lower dust optical depth (the atmosphere was more transparent) than in MY25 and MY26 [98,99]. The albedo values in MY24 should thus be the most representative of the mean surface materials, being least affected by scattering due to atmospheric dust.…”
Section: Datamentioning
confidence: 99%
“…Several regions of Mars were subjected to focused study, including Amazonis Planitia (where many dust devils have been found previously: Cantor et al, 2002;Fisher et al, 2005;Cantor et al, 2006), Chryse Planitia and Syria Planum. Chryse Planitia was chosen, because it is a northern lowland including the Viking 1 and Pathfinder landing sites, which are known as active dust devil areas, and Syria Planum, because it is a known region for dust devils and dust storms.…”
Section: Spatial and Temporal Distribution And Dimensionsmentioning
confidence: 99%